Improving Adolescent Reproductive Health Through Dysmenorrhea Gymnastics Education at The PSBR Dormitory, Blitar City - Rahmawati, Anita; Nurmawati, Thatit; Wulandari, Nawang; Yanuar, Dita (Journal of Community Service for Health, 2021)
Dysmenorrhea is often occurred at the beginning of menstruation, especially in adolescents. If left untreated, pain experienced by adolescents with primary dysmenorrhea could lead to serious problems that ultimately require health services and could also reduce quality of reproductive health and general body health. The aim of gymnastics activity is to improve the reproductive health of adolescent women through the provision of dysmenorrhea gymnastics education. The activity was divided into 2 sessions, lecture and practice. The first session were explanations, questions and answers about the menstrual cycle, dysmenorrhoea and how to prevent or treat dysmenorrhoea pain using dysmenorrhea gymnastics. The second one was gymnastics practice in the same time between community service team and all of the participants, where the service team was divided as gymnastics instructor and the others as facilitator who correct participants' exercise movements that were not right. This activity was carried out on young women at the PSBR dormitory in Blitar City. Implementation was in the March 2021 and followed by 35 teenagers. The results of this activity indicated that all of the participants were able to follow and carry out activities that have been planned properly. Dysmenorrhea gymnastics were an easy, cheap and safe way to reduce and prevent dysmenorrhea pain so that it could be an independent dysmenorrhea therapeutics option for adolescents, especially teenagers in the PSBR dormitory in Blitar City